2020
DOI: 10.1111/jse.12684
|View full text |Cite
|
Sign up to set email alerts
|

First fossil fruits of Elaeocarpus (Elaeocarpaceae) in East Asia: Implications for phytogeography and paleoecology

Abstract: The genus Elaeocarpus contains approximately 360 species and occurs in mesic forest communities from India, through to China, Southeast Asia, New Guinea, Australia, and New Caledonia. Elaeocarpus fossils are best known from the Eocene to the Miocene of Australia and the late Pliocene-early Pleistocene of India, but have not been documented from East Asia before. Here we describe six new species of Elaeocarpus, E. nanningensis sp. nov. from the late Oligocene Yongning Formation of the Nanning Basin, E. presikki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Lastly, attention should be paid to the inconsistencies between fossil and genetic evidence. Several fossil sited and many evergreen elements have been found in EBLFs, such as Castanopsis nanningensis , C. guangxiensis , Elaeocarpus nanningensis , and Lithocarpoxylon nanningensis in the Yongning Formation (Huang et al, 2018 ); Mahonia ningmingensis in the Ningming Formation (Hu et al, 2017 ); Elaeocarpus presikkimensis in the Erzitang Formation; and Elaeocarpus prerugosus , E. prelacunosus , E. preserratus , and E. preprunifolioides in the Foluo Formation (Liu et al, 2022 ). Geological ages of these formations range from the Oligocene to the late Miocene (Hu et al, 2017 ; Huang et al, 2018 ; Liu et al, 2022 ), indicating that EBLFs may have even earlier origins than suggested by phylogenetic reconstructions based on genetic data.…”
Section: Caveatsmentioning
confidence: 99%
“…Lastly, attention should be paid to the inconsistencies between fossil and genetic evidence. Several fossil sited and many evergreen elements have been found in EBLFs, such as Castanopsis nanningensis , C. guangxiensis , Elaeocarpus nanningensis , and Lithocarpoxylon nanningensis in the Yongning Formation (Huang et al, 2018 ); Mahonia ningmingensis in the Ningming Formation (Hu et al, 2017 ); Elaeocarpus presikkimensis in the Erzitang Formation; and Elaeocarpus prerugosus , E. prelacunosus , E. preserratus , and E. preprunifolioides in the Foluo Formation (Liu et al, 2022 ). Geological ages of these formations range from the Oligocene to the late Miocene (Hu et al, 2017 ; Huang et al, 2018 ; Liu et al, 2022 ), indicating that EBLFs may have even earlier origins than suggested by phylogenetic reconstructions based on genetic data.…”
Section: Caveatsmentioning
confidence: 99%
“…Rudraksha beads, which are essentially dried seeds from the tree, stand out as the most expensive and valuable seeds worldwide. This family includes 360 Elaeocarpus species, with 25 thriving in India's Gangetic plains and Himalayan regions [1]. In Tamil Nadu alone, researchers have identified eleven Elaeocarpus species, eight of which are specifically found in the Western Ghats.…”
Section: Introductionmentioning
confidence: 99%